Analisis Pengaruh Promosi, Harga, dan Desain Produk terhadap Keputusan Pembelian Konsumen : Studi Kasus pada Konveksi Nida Collection Adiwerna Kabupaten Tegal - Muslikhin Muslikhin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of promotion, price, and product design on consumer purchasing decisions at Nida Collection, a home-based garment business located in Adiwerna, Tegal Regency. The research is motivated by the increasing competition in the garment industry and the shift in consumer behavior that demands more effective marketing strategies. This study employs a descriptive qualitative approach with data collected through in-depth interviews, observations, and documentation. The research subjects include the business owner, marketing staff, and regular customers of Nida Collection. Data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that promotion has the most dominant influence on purchasing decisions, followed by product design and price. Social media promotion effectively enhances consumer awareness, increases purchase intention, and expands market reach. Competitive pricing that aligns with product quality also plays a crucial role in consumer decision-making. Additionally, attractive and trend-oriented product designs strengthen consumer preference and satisfaction. The study concludes that the synergy among promotion, price, and product design is a key determinant of consumer purchasing behavior in the local garment industry. These findings provide practical implications for micro, small, and medium enterprises (MSMEs) in developing more adaptive and consumer-oriented marketing strategies.